Contact mechanics in tribological and contact damage-related problems: a review - Li, Biao (2022)
When two bodies are in contact, various surface/subsurface damage problems may arise, which significantly shorten the service lives of functional components. These damage problems may further interact with one another and be influenced by such factors as friction and lubrication. Contact mechanics plays an important role in understanding the complex phenomena and analyzing the damage evolution. This paper aims to provide a comprehensive review of the recent progress in contact mechanics for tribological and contact damage–related problems. After a brief introduction of the contact mechanics, the applications of contact mechanics in various problems are systematically elaborated. Finally, the review concludes with future perspectives and major challenges to be addressed.